2017
DOI: 10.3102/0002831217732335
|View full text |Cite
|
Sign up to set email alerts
|

Improving Young English Learners’ Language and Literacy Skills Through Teacher Professional Development: A Randomized Controlled Trial

Abstract: Using a randomized controlled trial, we tested a new teacher professional development program for increasing the language and literacy skills of young Latino English learners with 45 teachers and 105 students in 12 elementary schools. School-based teams randomly assigned to the intervention received professional development focused on cultural wealth, high-impact instructional strategies, and a framework for collaboration. We observed each teacher three times during the school year and assessed students indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 29 publications
7
33
0
1
Order By: Relevance
“…Our finding is congruent with the existing literature showing first-year quality support for novice teachers is crucial in their instructional performance and in developing their beliefs and practices that allow them to navigate the challenges of first-year teaching (Allen, 2013). We also consider several of the specific supports in this study as consistent with the research literature that value teachers collaborating and learning in collaboration, particularly to improve their work with multilingual learners (e.g., Babinski et al, 2018; Martin-Beltran & Peercy, 2014; Peercy et al, 2015). Based on the existing literature, our theoretical perspective, and our findings, it appears that supporting first-year teachers through meaningful collaborative experiences can impact their perceptions of preparedness to work with multilingual students.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Our finding is congruent with the existing literature showing first-year quality support for novice teachers is crucial in their instructional performance and in developing their beliefs and practices that allow them to navigate the challenges of first-year teaching (Allen, 2013). We also consider several of the specific supports in this study as consistent with the research literature that value teachers collaborating and learning in collaboration, particularly to improve their work with multilingual learners (e.g., Babinski et al, 2018; Martin-Beltran & Peercy, 2014; Peercy et al, 2015). Based on the existing literature, our theoretical perspective, and our findings, it appears that supporting first-year teachers through meaningful collaborative experiences can impact their perceptions of preparedness to work with multilingual students.…”
Section: Discussionsupporting
confidence: 59%
“…Because of our finding that supportive teacher induction practices, particularly grounded in collaboration, impact teachers-perceived preparedness to work with multilingual students, we suggest further development and research of strong collaboratively based induction practices that particularly focus on developing strong teachers of multilingual learners. The research literature suggests inter-disciplinary collaborations that include both language specialists and general education teachers are particularly helpful (Babinski et al, 2018; Martin-Beltran & Peercy, 2014; Peercy et al, 2015). Finally, it is clearly important for teachers to have the opportunities to learn about and work directly with multilingual students.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted with both preservice (Galguera, 2011; Jimenez-Silva & Olson, 2012) teachers, as well as in-service teachers (Brancard & Quinnwilliams, 2012) found that collaborative PD opportunities supported learning. A relatively large subset of studies found that collaborative PD between mainstream teachers and language specialists was productive in multiple ways for teacher learning, practice, and the development of a shared sense of responsibility for teaching multilingual students (Babinski, Amendum, Knotek, Sánchez, & Malone, 2018; DelliCarpini & Alonso, 2014; English, 2009; Martin-Beltrán & Peercy, 2014; Peercy & Martin-Beltrán, 2012; Peercy, Martin-Beltrán, Silverman, & Nunn, 2015; Russell, 2014, 2015; Vázquez, López, Segador, & Mohedano, 2015). Other studies highlighted the productivity of various configurations of difference and heterogeneity in partnership (Collins & Liang, 2014; Estapa, Pinnow, & Chval, 2016; Molle, 2013), illustrating the value of teachers learning to talk across difference and engage with tools and perspectives that push their thinking.…”
Section: A Complex Portrait: Quality Content Teaching For Multilinguamentioning
confidence: 99%
“…Teacher PD is understood as activities that improve teachers' knowledge, skills, and attitudes of teaching practices (OECD 2014a). Literature has shown that teacher PD promotes teacher knowledge, skills, and performances (Babinski et al 2018;Desimone 2009;Garet et al 2001); teachers' efficacy (Butler et al 2015); job satisfaction (Ma and Mac-Millan 1999); positive school climates (Butler et al 2015;Hargreaves 2007); and student learning (Jacob et al 2017;Panero and Talbert 2013). Thus, many school reform movements have viewed teachers' participation in PD as key to changing teachers' beliefs and practices, student learning, and the implementation of educational policies (Villegas-Reimers 2003).…”
Section: Teacher Professional Development and Principal Supportmentioning
confidence: 99%